Pyridoxamine alleviates mechanical allodynia by suppressing the spinal receptor for advanced glycation end product-nuclear factor-κB/extracellular signal-regulated kinase signaling pathway in diabetic rats. (April 2020) - Zhang, Xin; Xu, Li; Chen, Weiyun; Yu, Xuerong; Shen, Le; Huang, Yuguang
Diabetic neuropathic pain is a common complication of diabetes mellitus and requires a substantial amount of societal resources. Pyridoxamine is an inhibitor of advanced glycation and lipoxidation end products. Several animal and clinical studies have confirmed that pyridoxamine can inhibit a range of pathological changes in diabetes-induced organ injury and alleviate certain kinds of neuropathic pain. However, no studies have attempted to explore the effects of pyridoxamine on diabetic neuropathic pain. We conducted animal experiments to examine whether pyridoxamine could alleviate diabetic neuropathic pain and to explore the mechanism underlying these effects. Adult male Sprague Dawley rats were randomly assigned to the normal + sterile water group, diabetic + sterile water group, diabetic + pyridoxamine100 group, diabetic +pyridoxamine200 group, diabetic + pyridoxamine400 group, or normal + pyridoxamine group. The rats in the diabetic +pyridoxamine100, diabetic + pyridoxamine200, diabetic + pyridoxamine400, and normal + pyridoxamine groups received pyridoxamine at dosages of 100 mg/kg/day, 200 mg/kg/day, 400 mg/kg/day, and 400 mg/kg/day, respectively, via intragastric administration. The rats in the other groups received water daily. Pyridoxamine alleviated diabetic neuropathic pain at least partially by suppressing the activity of the spinal receptor for advanced glycation end products-nuclear factor-κB/extracellular signal-regulated kinase signaling pathway; additionally, pyridoxamine decreased advanced glycation end product-modified low-density lipoprotein, oxidized low-density lipoprotein, and interleukin-1β levels in the serum. The immunofluorescence staining results revealed that most phosphorylated nuclear factor-κB was localized to neuronal cells and not to microglia or astrocytes; this pattern may be associated with the upregulated expression of pain-related proteins. The abovementioned results indicate that pyridoxamine is a promising choice for the clinical treatment of diabetic neuropathic pain. Further investigations need to be carried out to confirm the benefits of pyridoxamine.